Methods of translating non-equivalent legal vocabulary - Iunda D. R. (History of culture, study of art and philology: modern points of view, 2020)
the article touches upon a subject of non-equivalent vocabulary. Translating legal terms, which primarily include legal realias, denoting concepts, that are not present in the target language, is a rather difficult procedure.
Keywords: безэквивалентная лексика; non-equivalent vocabulary; юридический перевод; legal translation